2021
DOI: 10.1149/2162-8777/ac39a6
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Self-Assembled Composite Abrasives for Chemical Mechanical Polishing of A-Plane Sapphire

Abstract: Sapphire substrates with different orientations have wide applications due to their excellent physical, chemical and optical properties. However, the chemical mechanical polishing of sapphire is challenging due to its chemical inertness, extreme hardness and brittleness. Herein, chemical mechanical polishing of A- and C-plane sapphire was systematically studied using α-Al2O3 and silica abrasives and polishing mechanism was analyzed by X-ray photoemission spectroscopy (XPS) and nanoindentation meter. The high M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, Vovk et al believed that silica abrasives undergo a chemical reaction, as shown in Formulas ( 6)-( 8), in which a layer of Al 2 SiO 5 aluminum silicate at a thickness of 20.5 nm was formed on the surface of sapphire during the CMP process, which was then removed using silica abrasives [54]. Yu et al also demonstrated the formation of Al 2 SiO 5 [55]. All in all, regardless of the compound formed by silica sol and alumina, the recognized mechanism is that at the interface between the abrasive and the sapphire, the solid-solid reaction between the sapphire and the abrasive will occur, forming a soft layer, which is conducive to the removal of the sapphire.…”
Section: The Mechanism Of Sapphire Polishingmentioning
confidence: 99%
“…However, Vovk et al believed that silica abrasives undergo a chemical reaction, as shown in Formulas ( 6)-( 8), in which a layer of Al 2 SiO 5 aluminum silicate at a thickness of 20.5 nm was formed on the surface of sapphire during the CMP process, which was then removed using silica abrasives [54]. Yu et al also demonstrated the formation of Al 2 SiO 5 [55]. All in all, regardless of the compound formed by silica sol and alumina, the recognized mechanism is that at the interface between the abrasive and the sapphire, the solid-solid reaction between the sapphire and the abrasive will occur, forming a soft layer, which is conducive to the removal of the sapphire.…”
Section: The Mechanism Of Sapphire Polishingmentioning
confidence: 99%
“…In addition, sapphire is chemically inert and hence does not react with acids at room temperature and is an excellent electrical insulator with high permittivity (Xu et al , 2018; Zhang et al , 2021). It is used in several fields such as the military, aerospace industry, biomedical industry and lighting-display field (Zhankui et al , 2021; Yu et al , 2021). The surface of sapphire wafers for light emitting diode ( LED) substrates should be ultra-smooth and damage-free (Uhlmann et al , 2018; Shi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As the best global planarization technology, chemical mechanical polishing (CMP) has been widely used in processing various substrate materials, optical crystals, and metals. [4][5][6][7][8][9][10][11][12][13] Through the synergy of chemical etching and mechanical abrasion, an ultra-smooth and defect-free surface can be achieved.…”
mentioning
confidence: 99%